2016
DOI: 10.1038/ng.3625
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in MHC proteins is associated with T cell receptor expression biases

Abstract: Within each individual, a highly diverse T cell receptor (TCR) repertoire interacts with peptides presented by major histocompatibility complex (MHC) molecules. Despite extensive research, it remains controversial whether germline-encoded TCR-MHC contacts promote TCR-MHC specificity and if so, whether there exist differences in TCR V-gene compatibilities with different MHC alleles. We applied eQTL mapping to test for associations between genetic variation and TCR V-gene usage in a large human cohort. We report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
149
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(161 citation statements)
references
References 70 publications
10
149
1
1
Order By: Relevance
“…In general, the molecular basis for selection of biased TCR repertoires is not well understood, but has been suggested to involve a combination of preferences in the somatic rearrangement machinery (2) and germline-encoded features that influence thymic selection (3). A recent study showed a strong trans association between variation in the MHC locus and TCR variable (V) gene usage, further suggesting a codependent expression pattern (4). However, it is still unclear if and how certain TCR V genes are predisposed to interact with MHC and underlie the existence of biased repertoires.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the molecular basis for selection of biased TCR repertoires is not well understood, but has been suggested to involve a combination of preferences in the somatic rearrangement machinery (2) and germline-encoded features that influence thymic selection (3). A recent study showed a strong trans association between variation in the MHC locus and TCR variable (V) gene usage, further suggesting a codependent expression pattern (4). However, it is still unclear if and how certain TCR V genes are predisposed to interact with MHC and underlie the existence of biased repertoires.…”
Section: Introductionmentioning
confidence: 99%
“…The fact this does not happen leads to an intrinsic bias between TCRs and A*0201 by definition. Similar features of evolved compatibility, with ranges of compatibility and strengths of interatomic “glue” likely exist elsewhere between TCR and MHC proteins, contributing to the genetic linkage detected by Sharon et al [10]. …”
mentioning
confidence: 70%
“…The recent studies of Sharon et al . published in Nature Genetics provide evidence for this link [10]. Using expression quantitative trait loci (eQTL) analysis, the authors show linkage between multiple MHC and TCR genes.…”
mentioning
confidence: 99%
“…There has been a long held theory of a co-evolution of MHC and TCR (2628), which has interested us as well (29). Analysis of this co-evolution is predominantly based on CDR1 and CDR2 contributions as these are the major germ-line components that define the V region, and on which selection and thus evolution can function.…”
Section: Discussionmentioning
confidence: 99%